Pengaruh Profitabilitas, Kebijakan Dividen, dan Struktur Modal terhadap Nilai Perusahaan (Studi pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Vanessa Meisyang Tatuil; David P. E. Saerang; Steven J. Tangkuman (Riset Akuntansi dan Portofolio Investasi, 2026)
This study examines the effect of probability, dividend policy, and capital structure on firm value in banking subsector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024. The research is grounded in Signaling Theory and the Efficient Market Hypothesis, explaining how financial performance interpreted by investors and reflected stock prices. A quantitative approach is employed using secondary data, collected through documentation of published financial statements and market data from the IDX. Samples were selected using purposive sampling, resulting in 17 firms. Variables were measured using ROA (profitability), DPR (dividend policy), DER (capital structure), and PBV (firm value). Data were analyzed using multiple linear regression (SPSS) along with classical assumption tests. The findings indicate that profitability (ROA) has a positive and significant effect on firm value, while dividend policy (DPR) has a negative but insignificant effect, and capital structure (DER) shows a positive and significant effect. Simultaneously, the three independent variables have a significant influence on firm value, with the model explaining 51,2% of the variance. In conclusion, profitability is the most dominant factor in enhancing the firm value of banking companies during the study period.